2021
DOI: 10.1007/s00592-020-01644-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal triglycerides and disturbed glucose metabolism in pregnancy

Abstract: Aims Dyslipidemia in pregnancy is associated with adverse pregnancy outcomes as elevated triglycerides might be considered as a risk factor for hyperglycemia and gestational diabetes. As only a few studies have addressed the association between maternal triglycerides and glucose metabolism, we aimed to explore the pathophysiologic associations of moderate hypertriglyceridemia and maternal glucose metabolism in pregnancy. Methods Sixty-seven pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
2
17
0
1
Order By: Relevance
“…Established risk factors for GDM include ethnicity, obesity, and family history of diabetes [26,27], while lower insulin sensitivity, use of insulin therapy, pre-pregnancy obesity, severity of GDM and high HbA1c levels during pregnancy were identified as independent predictors of subsequent diabetes in previous observational studies [28][29][30], in line with our data. Our study adds novel information about their interaction and their priority in identifying specific phenotypes.…”
Section: Comparison With Existing Datasupporting
confidence: 90%
“…Established risk factors for GDM include ethnicity, obesity, and family history of diabetes [26,27], while lower insulin sensitivity, use of insulin therapy, pre-pregnancy obesity, severity of GDM and high HbA1c levels during pregnancy were identified as independent predictors of subsequent diabetes in previous observational studies [28][29][30], in line with our data. Our study adds novel information about their interaction and their priority in identifying specific phenotypes.…”
Section: Comparison With Existing Datasupporting
confidence: 90%
“…The result indicated that 34.8% of the GDM risk could be attributed to the presence of interaction between thyroid hormone and TG levels in pregnant women. Dyslipidemia during pregnancy, especially hypertriglyceridemia, was closely associated with a greater risk of GDM [21,45], and the possible mechanisms including impaired insulin action, β-cell function, and nitric oxide signaling [21,46]. As shown by a previous study, FT3/FT4 ratio was positively associated with multiple risk factors for GDM, including homeostasis model assessment of insulin resistance (HOMA-IR), waist circumference, triglyceride levels, fasting blood glucose, and systolic blood pressure [47].…”
Section: Discussionmentioning
confidence: 97%
“…Several cross-sectional studies have shown that the free triiodothyronine (FT3)/free thyroxine (FT4) ratio, a commonly used indicator for thyroid function, is associated with higher insulin resistance, glycated hemoglobin, fasting glucose, post-load glucose levels, and increased risk of GDM in pregnancy women [19,20 ]. Dyslipidemia was also associated with insulin resistance and β-cell dysfunction in pregnant women [21] and was found to be an independent predictor for GDM [22]. Moreover, there was evidence that thyroid dysfunction may also be a risk factor for dyslipidemia [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertriglyceridemia has been related to impaired insulin action and β-cell function in pregnancy. This molecular mechanism has been associated with a higher risk of developing GD, even in the case of moderately elevated levels [41][42][43]. However, to our knowledge, there is insufficient evidence on the effects of standard treatment for diabetes on hypertriglyceridemia [44].…”
Section: Maternal Triglyceridesmentioning
confidence: 99%